Characterization and phylogenetic analysis of the complete mitochondrial genome of Aphis spiraecola (Hemiptera: Aphididae). Issue 2 (3rd July 2019) - Du, Yimin; Liu, Xinjun; Wang, Ying; Lu, Zhanjun
Abstract: Aphis spiraecola is an important pest of citrus and transmits a number of plant viruses. Here, we sequenced and annotated the complete mitochondrial genome (mitogenome) of A. spiraecola . This mitogenome was 15, 465 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and 2 ribosomal RNA unit genes (rRNAs). Gene order was conserved and identical to that of Drosophila yakuba and to most other previously sequenced Aphididae. The whole mitogenome exhibited heavy AT nucleotide bias (81.8%). All 13 PCGs were initiated by the ATN (ATG, ATT and ATA) codon. Except for cox1 and nad4 which end with the incomplete codon T−, all PCGs terminated with the stop codon TAA. Phylogenetic analysis showed that A. spiraecola got together with the same genus species Aphis gossypii and Aphis craccivora with high support value, and Aphis had a close relationship with Schizaphis and Rhopalosiphum .